Flow-mediated dilation can be used to predict incident hypertension in patients with hyperuricemia - Chunli Han; Zhanchao Xian; Yang Zou; Zhiyong Liao; Rongfeng Yang; Chunxia Zou; Xiaoqing Wang; Yan Sun (Archives of Medical Science, 2019)
Introduction The aim of the study was to evaluate whether flow-mediated dilation (FMD) can be used to predict incident hypertension in patients with hyperuricemia.